Criteria Measurement and Evaluation System of Functioning Efficiency of Ukraine’s Regional Landscape - MEDVID, Viktoriia; USTIK, Tetiana; LYSHENKO, Margarita; KOVBASA, Oleksandr (Journal of Advanced Research in Law and Economics, 2019)
The article focuses on the actual scientific problem of contradictions overcoming in progressive development of Ukraine's regions using methodical tools of comparative evaluation of the capacity and efficiency of regional economies. Current national and international approaches to assess the functioning efficiency of Ukraine’s regional landscape have been analyzed. Groups of statistical indicators that should be used when assessing the level of regional economic development have been singled out. The author has improved criteria measurement and evaluation system of functioning efficiency of the regional landscape that, unlike the current practice, are based on the determination of aggregated indicators for sustainable development. It will form a complex specification for the use of space and resources available to identify possible economic development capacity. The article substantiates the possible factors of comparative aggregated indicators ratio transition from one type to another one. Approbation of methodical tools was carried with reference to Ukraine’s regions. On the base of it aggregated indicators of capacity and efficiency were calculated. Determination of ratio types of common comparative indices of functioning capacity and efficiency of the regional landscape made it possible to identify optional factors of the transition from one type to another one (in economic development). The basic imperatives and strategic directions of modern regional development through the use of space and resource capacities are formulated.